Pengaruh Etika Bisnis Islam Dalam Meningkatkan UMKM : Studi Literature - Aji Argo Putro; Dety Mulyanti (Dharma Ekonomi, 2023)
The article titled "The Influence of Islamic Business Ethics in Enhancing UMKM" by Manna et al. elaborates on how Micro, Small, and Medium Enterprises (UMKM) are one of the solutions to address economic challenges in society. However, UMKM entrepreneurs often encounter various challenges in running their businesses, which has led to the emergence of the Islamic economic system as a solution to these problems. In applying Islamic business ethics, there are several rules that must be followed. This research uses a qualitative research method and a literature review approach by searching for several relevant journals and articles about the application of Islamic business ethics in enhancing UMKM. The results of this study indicate that the application of Islamic business ethics needs to be implemented to increase awareness in business practices. The application of Islamic business ethics also has a positive impact on enhancing UMKM.